Remember me : a novel - Hendrie, Laura, 1954- (New York : Henry Holt and Company, 1999)
Meet Rose Devonic, a wily, ferociously determined twenty-nine-year-old woman. In the tiny mountain town of Queduro, New Mexico, she makes her living selling traditional embroidery. But Rose has no home or family. In winter she sleeps in a mostly abandoned motel, and in summer she lives out of her car. A tragedy in her past, which is a constant reminder to her neighbors of their complicity, has made her an outcast who trusts nothing except her own ability to survive. One frozen afternoon in October, Rose hitches a ride over the already snow-covered mountain pass and walks the last four miles of the road to her hometown of Queduro. Her monthlong fling with Harmon Waters - yet another disappointment - is over, and once again she must pick up the pieces of her life. But when she arrives at the Ten Tribes Motel, even Birdie, her elderly landlord and best friend, seems dismayed to see her.
Keywords: MUJERES -- NOVELA; NOVELA ESTADOUNIDENSE